The curvilinear responses of biomass accumulation and root morphology to a soil salt-nitrogen environment reflect the phytodesalination capability of the euhalophyte Suaeda salsa L. - Wang, Yanyan; Guo, Tongkai; Tian, Changyan; Zhao, Zhenyong; Zhang, Ke; Mai, Wenxuan (Frontiers in Plant Science, 2024)
Under the sufficient nitrogen supply, it is of great significance to investigate the law of biomass allocation, root morphological traits, and the salt absorption capacity of euhalophytes to evaluate their biological desalination in saline soil. Although the curvilinear responses of biomass accumulation and root morphology in response to soil salinity have been recognized, these perceptions are still confined to the descriptions of inter-treatment population changes and lack details on biomass allocation in organs at an individual level. In this study, Suaeda salsa was grown in root boxes across a range of soil salt levels. The study showed that their growth and development were significantly affected by soil soluble salts. The law of biomass allocation was described as follows: increased soil soluble salts significantly increased the leaf mass ratio and decreased the stem mass ratio, and slightly increased the root mass ratio among treatments. For individuals at each treatment, leaf mass ratio > stem mass ratio > root mass ratio, except in the control treatment at the flower bud and fruit stages. Biomass responses of the control treatment indicated that salt was not rigorously required for Suaeda salsa in the presence of an adequate nitrogen supply, as verified by the correlation between biomass, nitrogen, and soil soluble salt. Salt could significantly inhibit the growth of Suaeda salsa (P<0.01), whereas nitrogen could significantly promote its growth (P<0.01). Root morphology in response to soil soluble salts showed that salt acquisition by the root was highest at a salt level of 0.70%, which corresponds to light saline soil. Consequently, we conclude that phytodesalination by Suaeda salsa was optimal in the light saline soil, followed by moderate saline soil.